Prenatal Carrier Screening for Spinal Muscular Atrophy - Wood, S. Lindsay; Brewer, Fallon; Ellison, Rebecca; Biggio, Joseph R.; Edwards, Rodney K. (American Journal of Perinatology, 2016)
Introduction Spinal muscular atrophy (SMA), a neurodegenerative genetic disorder, affects 1:5,000 to 1:10,000 infants. Carrier rates are 1:25 to 1:50. We implemented ACOG-endorsed prenatal SMA screening in mid-2014 and sought to assess uptake, observed carrier rate, and providers' knowledge and attitudes toward genetic conditions and carrier screening.Methods Retrospective cohort study of all patients receiving prenatal genetic counseling at our institution from August 2014 to April 2015. Factors associated with screening uptake were assessed. Proportions who accepted screening, were screen-positive, had partners tested, had partners who were screen-positive, and had fetuses tested were calculated. Providers' knowledge and attitudes were assessed using a validated questionnaire.Results Of 1,158 patients offered SMA screening, 224 accepted (19.3%, 95% CI 17.2–21.7). Uptake differed by race, parity, religion, and genetic counselor seen. Five (2.2% or 1:45, 95% CI 0.8–5.3 or 1:19–1:125) women were identified as carriers. Of 3 partners screened, none screened positive (0%, 95% CI 0–5.3). There were no prenatal SMA diagnoses (0%, 95% CI 0–1.4). Of 90 survey respondents, 42% incorrectly answered 1 of 9 knowledge questions. Provider attitudes toward screening were contradictory.Conclusion Despite significant resources utilized, prenatal SMA carrier screening identified no fetal cases. Cost-effectiveness and other barriers should be considered prior to large-scale adoption of more comprehensive genetic screening.
Keywords: carrier screening; expanded carrier screening; genetic screening; prenatal genetics; SMA; spinal muscular atrophy